2021
DOI: 10.3390/ani11030746
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chamber Cardiac Pacemaker Implantation in a Donkey with Complete AV Block: A Long-Term Follow-Up

Abstract: A five-month-old African jenny was presented with a history of exercise intolerance and syncopal episodes. Severe bradycardic arrhythmia due to a high-grade second-degree atrioventricular (AV) block with progression to complete AV block was diagnosed. The jenny underwent a transvenous single-chamber pacemaker implantation. The implantation procedure was performed in a lateral recumbency and the ventricular lead was inserted through the jugular vein. Positioning of the lead was guided by echocardiography. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The cause of their third‐degree AV block was not known, but a genetic predisposition has been suggested. 16 , 17 Intermittent AV conduction with abnormal QRS morphology, possibly caused by bundle branch block, and paroxysmal ventricular tachycardia also were identified. Two donkeys were diagnosed with aortic root aneurysm several centimeters distal to the aortic valve, which remained stable during the follow‐up period (3 and 6 years).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cause of their third‐degree AV block was not known, but a genetic predisposition has been suggested. 16 , 17 Intermittent AV conduction with abnormal QRS morphology, possibly caused by bundle branch block, and paroxysmal ventricular tachycardia also were identified. Two donkeys were diagnosed with aortic root aneurysm several centimeters distal to the aortic valve, which remained stable during the follow‐up period (3 and 6 years).…”
Section: Discussionmentioning
confidence: 98%
“…In this report, all of the donkeys were miniature donkeys. The cause of their third‐degree AV block was not known, but a genetic predisposition has been suggested 16,17 . Intermittent AV conduction with abnormal QRS morphology, possibly caused by bundle branch block, and paroxysmal ventricular tachycardia also were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The critical moment of pacemaker implantation in large animals lies on the placement of a transvenous temporary pacemaker, if possible, before the administration of any sedative drugs. Sedlinská et al 8 reported several episodes of asystole requiring indirect cardiac massage in a 5-month-old donkey undergoing pacemaker implantation and in which t e m p o r a ryp a c i n gw a sn o tp o s s i b l e .T h eu s eo fat e m p o r a ry cardiac pacemaker before anaesthesia will allow emergency pacing in the situation of severe bradycardia or asystole 1,5,8 and remains the only method for temporary pacing in adult equids, as transcutaneous external pacing is limited by the size of the animal. A further advantage of transvenous pacing is the possibility for pacing on the awake standing animal, wh e r ea sth i si sn o tpo s s i b l eu s i n gatr a n scu ta n eo u sm e th od .…”
Section: Discussionmentioning
confidence: 99%
“…The critical moment of pacemaker implantation in large animals lies on the placement of a transvenous temporary pacemaker, if possible, before the administration of any sedative drugs. Sedlinská et al 8 . reported several episodes of asystole requiring indirect cardiac massage in a 5‐month‐old donkey undergoing pacemaker implantation and in which temporary pacing was not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation